Standalone Hybrid Power System for a Rural Destination in India: An Economic Analysis - Mohanty, Sthitapragyan (International Journal of Computer Sciences and Engineering, 2025)
Demand of energy in isolated parts of India is solved by extension of grid power supply but it is not economical at all as cost varies depending upon distance,land and load demand.In view of this problem,supply of power to remote area demands advanced skill with updated technical and economical strategies.Because of that expensive and insufficient grid power in rural places have been replaced by renewable energy sources.So this particular work chooses the best hybrid technology for rural electric generation for a village area in Bhubaneswar. The solution obtained from using HOMER software presents the economic feasibility of the hybrid generation system for a rural conglomerate in Ghatikia, Bhubaneswar with latitude 20.26 0 N and longitude 85.76 0E.This paper contains four different type of Hybrid configuration. The optimization result obtained by using a hybrid conﬁguration composed of a wind energy system, a solar PV system and a diesel generator used as a backup system.